Application of Finite Difference Time Domain (FDTD) Method to Calculate Poynting Vector of EM Waves in Free Space - Farhat, Sedig S. (The Libyan Journal of Science, 2022)
In this paper, the implements of a numerical approach utilizing the finite difference time domain (FDTD) method was applied in three dimensional electromagnetic wave formulations and the computational domain can be updated explicitly. This calculation based on solving Maxwell's curl equations by utilizing the FDTD. The space has been excited for a short duration by three sinusoidal signals at the centre of the space and in three different locations. To allow for comparison between the models, the signals generated by means of a variety of positions. This study showed that the Poynting vector components intensities had changed due to the addition of sources in the space. It was noted that Poynting vector image intensities were variances which depend on the location of the excitation pulse. Dependent on the position of the source whether it is close in proximity or spread apart from one another. Therefore, the greater the source distribution the larger volume covered in the space.